2009
DOI: 10.1016/j.physrep.2009.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Cosmological perturbations

Abstract: We review the study of inhomogeneous perturbations about a homogeneous and isotropic background cosmology. We adopt a coordinate based approach, but give geometrical interpretations of metric perturbations in terms of the expansion, shear and curvature of constant-time hypersurfaces and the orthogonal timelike vector field. We give the gauge transformation rules for metric and matter variables at first and second order. We show how gauge invariant variables are constructed by identifying geometric or matter va… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
883
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 551 publications
(898 citation statements)
references
References 124 publications
(256 reference statements)
13
883
1
1
Order By: Relevance
“…One of the conditions for the conservation of ζ on super-horizon scales is that the anisotropic part of the stress-energy tensor vanishes in that regime [50]. This is the case for minimally coupled scalar fields with x−independent vev [53]. In the present model, however,…”
Section: Scalar Curvature Perturbations On the Frw Solutionmentioning
confidence: 75%
“…One of the conditions for the conservation of ζ on super-horizon scales is that the anisotropic part of the stress-energy tensor vanishes in that regime [50]. This is the case for minimally coupled scalar fields with x−independent vev [53]. In the present model, however,…”
Section: Scalar Curvature Perturbations On the Frw Solutionmentioning
confidence: 75%
“…Recent analyses [41][42][43][44][45][46][47][48] of multifield models showed that unlike the single-field models they generically provide density (entropy) perturbations which can induce the curvature perturbation to evolve beyond the cosmological horizon in the process of inflation [49]. Evolution of density perturbations in multifield models should be studied in order to analyze new features in the observables such as non-Gaussianities [50] which are absent in the single-field inflationary models.…”
Section: Jhep12(2017)036mentioning
confidence: 99%
“…Then the spectral index n s and tensor-to-scalar ratio r at the time when a characteristic scale (50-65 e-foldings before the end of inflation) is of the order of the Hubble radius in the course of inflation, can be calculated using the single-field equations valid to lowest order in slow-roll parameters [48,49] n s = 1 − 6 + 2η σσ , r = 16 . …”
Section: Properties Of the Equations Of Motion In The Flrw Metricmentioning
confidence: 99%
“…Let us first note that, once nonlinear effects are taken into account, the separation of scalar, vector and tensor become impossible. This is well-known in GR when we consider secondorder perturbations, where all the sectors of the firstorder perturbations become the sources of the secondorder ones [50]. Taking these into account, let us consider the non-perturbative solutions of the type,…”
Section: Non-perturbative Cosmological Solutionsmentioning
confidence: 99%